Proces szkolenia personelu w doskonaleniu systemu zarządzania jakością - Giemza, Mariusz (Staff Training Process in Quality Management System Improving, 2008)
Implementation and improvement of quality management system begin many positive changes for the organization in its functioning, such as raising staff's qualifications by trainings. Running the preplanned trainings is one of the fulfillments described in ISO 9001:2000 standard. The organizations may use the requirements described in ISO 10015:1999 standard to lead the trainings. The idea of training process in Polish organizations that run under ISO 9001:2000 management system became an aim of the research. The paper presents questionnaire results analysis on type of training, training effectiveness evaluation, factors determining trainings and difficulties in leading the training in Polish organizations. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 402-412